The Invisible Powers: The Language of BusinessThe Invisible Powers: The Language of Business, by ClancyJohn J. Lexington, MA: Lexington Books, D. C. Heath and Company, 1989, 331 pp., $24.95, cloth. - Louis, Meryl Reis (Academy of Management Review, 1990)
The article presents a review of the book ?The Invisible Powers: The Language of Business,? by John J. Clancy.